2016
DOI: 10.1038/ncomms10515
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism for the biogenesis of outer membrane vesicles in Gram-negative bacteria

Abstract: Bacterial outer membrane vesicles (OMVs) have important biological roles in pathogenesis and intercellular interactions, but a general mechanism of OMV formation is lacking. Here we show that the VacJ/Yrb ABC (ATP-binding cassette) transport system, a proposed phospholipid transporter, is involved in OMV formation. Deletion or repression of VacJ/Yrb increases OMV production in two distantly related Gram-negative bacteria, Haemophilus influenzae and Vibrio cholerae. Lipidome analyses demonstrate that OMVs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
422
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(457 citation statements)
references
References 54 publications
23
422
0
1
Order By: Relevance
“…Therefore this avenue of investigation was not pursued further. These data thus confirmed that the observed increase in DNA release events under competence-inducing conditions was not due to increased cell death as a result of an iron deficiency nor was it likely due to increased biogenesis of outer-membrane vesicles known to occur in H. influenzae in response to iron starvation (60). Although competence has long been associated with the uptake of DNA, here we provide evidence that, in NTHI, induction of competence is also associated with the increased release of DNA and likely also the associated DNABII proteins.…”
Section: Resultssupporting
confidence: 75%
“…Therefore this avenue of investigation was not pursued further. These data thus confirmed that the observed increase in DNA release events under competence-inducing conditions was not due to increased cell death as a result of an iron deficiency nor was it likely due to increased biogenesis of outer-membrane vesicles known to occur in H. influenzae in response to iron starvation (60). Although competence has long been associated with the uptake of DNA, here we provide evidence that, in NTHI, induction of competence is also associated with the increased release of DNA and likely also the associated DNABII proteins.…”
Section: Resultssupporting
confidence: 75%
“…In Gram-negative bacteria, endolysin and the ABC transporter system positively affect MV production via different molecular mechanisms (45,46). How singlemembrane, Gram-positive bacteria that have a thick peptidoglycan cell wall produce MVs is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial OMVs can allow trafficking of biomolecules to other cells in their environment. Studies showed that OMVs are definitive components of the Pa and NTHI biofilm EPS (28,29), and they contain cargo that may contribute to the matrix EPS ( recently been identified (30), their precise role in modulating biofilm/EPS structure has not been evaluated.…”
Section: Outer Membrane Vesicles (Omvs)mentioning
confidence: 99%